Pkm Edukasi Penerapan 3M sebagai Upaya Pencegahan Covid-19 di Kel. Mayang Mangurai Kota Jambi - Nurfitriani Nurfitriani (3031-8572, 2022)
Infectious or infectious diseases are certain diseases (infections) that can pass from one person to another, either directly or indirectly . Until now, the world is facing a pandemic of infectious diseases, namely Corona Virus Disease (COVID-19). This disease is an outbreak in almost all countries, both developed and developing countries. One of the efforts to break the chain of transmission is through the implementation of health protocols by implementing the 3M protocol, namely washing hands, using masks and maintaining distance. Â This service aims to increase awareness of residents, especially mothers and children in RT 36 to always comply with health protocols with the implementation of 3M so that Covid-19 cases do not occur in the RT 36 Mayang Mangurai area. The method of implementing PKM is to provide education and demonstrations on how to wash hands properly, distribute leaflets on how to open and install the correct masks, and distribute cloth masks to participating mothers in the number of 30 people. As a result of this service, mothers and children can re-demonstrate how to properly open and install masks (6 0%), demonstrate how to wash hands properly (60%), increase knowledge about preventing the transmission of COVID-19. Â Â Especially for mothers, mothers are starting to realize and want to continue to comply with health protocols so that the health of all residents of RT 36 continues to improve. It is hoped that residents will continue to implement health protocols by means of 3M (washing, hands, maintaining distance and wearing masks).